Towards a Female Republic of Letters: (M) Raquel Adler`s Notes and Interventions in La Literatura Argentina (Buenos Aires, 1931-1936) - María Lucía Puppo (Estudios de Teoría Literaria)
Although mostly remembered as an author of religious poetry, Raquel Adler was also a critic, teacher, and promoter of women's writing. This paper proposes an approach to her figure and her journalistic and essayistic work, which reveals her as an active agent in the Argentine literary field of the 1930s. Specifically, we will examine the notes and reviews signed by Adler, as well as her other interventions, in the magazine La Literatura Argentina, where she was in charge of the “Female Books” section from its creation in 1931 until the magazine closed in 1936. We will observe how, from her various roles as writer, interviewer and critic, Adler contributed to making visible the works written by her peers, to underlining the consciousness of collective belonging to a “thinking” and “liberated” feminine and American tradition (De la Tierra 153), and to detect the demands of a largely female audience, eager for “voices unheard until now” (109). Even if on the one hand her writings praised feminine “sensitivity” and “spontaneity”, which, in her opinion, favored poetic writing, on the other hand, Adler advocated for the rights of women writers and, from Catholic and spiritualist circles, adhered to the feminist cause.